Minister of Supply and Internal Trade Ministerial Decree No. 67 of the year 2017 Issued on 26/3/2017 = وزارة التموين والتجارة الداخلية قرار وزارى رقم 67 لسنة 2017 صادر بتاريخ 26/3/2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic